Thoracic disc herniation causing transient paraplegia coincident with epidural anesthesia: A case report - Kaya, Arzu; Ozgocmen, Salih (My University, 2009)
Neurological deficits following epidural or spinal anesthesia are extremely rare. Transient paraplegia following epidural anesthesia in a patient with thoracic disc herniation has been presented. A 44-yearold woman developed paraplegia during the operation for vascular surgery of her legs under epidural anesthesia. Epidural hematoma or spinal cord ischemia was ruled out by magnetic resonance imaging of the thoracic and lumbar spine in which protruded disc at T11-12 level compressing the spinal cord has been verified. Patient responded well to steroid treatment and rehabilitation interventions. Physicians should be aware of preceding disc protrusions, which may have detrimental effects on spinal cord perfusion, as a cause of persistent or transient paraplegia before epidural anesthesia procedure. MRI is a valuable imaging option to rule out epidural anesthesia complications and coexisting pathologies like disc herniations. © 2009 Kaya and Ozgocmen; licensee Cases Network Ltd.
Keywords: etodolac; lidocaine; methylprednisolone; pentoxifylline; adult; anesthesia induction; article; case report; daily life activity; electrostimulation therapy; epidural anesthesia; epidural hematoma; female; hospital discharge; human; intervertebral disk hernia; leg varicosis; muscle training; neurologic disease; nuclear magnetic resonance imaging; osteophyte; paraplegia; partial thromboplastin time; patient positioning; prothrombin time; range of motion; rehabilitation care; spinal cord ischemia; steroid therapy; treatment response; vascular surgery